2009
DOI: 10.1159/000176037
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer-Producing Granulocyte Colony-Stimulating Factor

Abstract: An 86-year-old man with a serum prostate-specific antigen level of 93.33 ng/ml was diagnosed as having cT3aN0M0 prostatic adenocarcinoma of Gleason score 9. Although the serum prostate-specific antigen responded well to combined androgen blockade, the cancer spread and lead to death 6 months after diagnosis. The patient had leukocytosis during the clinical course with no sign of localized infection, especially after manipulation of the prostate. Enzyme immunoassay demonstrated elevated serum levels of granuloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Furthermore, our previous findings suggest a strong association between both G-CSF and G-CSFR in colon and gastric cancer metastasis ( 10 ). In agreement with these findings, in human tumors there are various reports of extremely aggressive G-CSF producing tumors in multiple cancer types, such as lung cancer ( 18 , 19 ), cervical cancer ( 20 ), meningioma ( 21 ), melanoma ( 22 ), breast cancer ( 8 ) and prostate cancer ( 23 ), demonstrating the important and modulatory effect of G-CSF in tumor progression and metastasis.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, our previous findings suggest a strong association between both G-CSF and G-CSFR in colon and gastric cancer metastasis ( 10 ). In agreement with these findings, in human tumors there are various reports of extremely aggressive G-CSF producing tumors in multiple cancer types, such as lung cancer ( 18 , 19 ), cervical cancer ( 20 ), meningioma ( 21 ), melanoma ( 22 ), breast cancer ( 8 ) and prostate cancer ( 23 ), demonstrating the important and modulatory effect of G-CSF in tumor progression and metastasis.…”
Section: Discussionsupporting
confidence: 78%
“…VEGF represents the prominent angiogenic factor that promotes the proliferation, survival, migration and tube formation of endothelial cells. We then examined, in untreated and EA treated LnCap cells, the levels of VEGF and others growth factors involved in prostate cancer progression such as Fibroblast growth factor (FGF), Granulocyte colony-stimulating factor (G-CSF), Hepatocyte growth factor (HGF) [47,48,49]. Moreover, since chronic inflammation has been suggested to favour prostate cancer development [50], the levels of Interleukin 15 (IL-15) were measured.…”
Section: Resultsmentioning
confidence: 99%
“…G-CSF productions by lung [14] and bladder [15] cancer cells have been reported to be associated with an invasive behavior of these cancer cells. Matsuoka et al reported a case of prostate cancer cells to produce G-SCF by immunohistochemical analyses, indicating its prognostic implications in prostate cancer outcome [16]. …”
Section: Introductionmentioning
confidence: 99%